1985
DOI: 10.1182/blood.v66.1.92.92
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and functional consequences of dissociation of the platelet membrane glycoprotein IIb-IIIa complex

Abstract: The platelet membrane glycoproteins, IIb and IIIa, form a Ca2+- dependent heterodimer complex that functions as the fibrinogen receptor in activated platelets to mediate platelet aggregation. Little is known about factors that affect the IIb-IIIa complex within the platelet membrane. It has been observed that platelets incubated with ethylene glycol tetra-acetic acid (EGTA) at 37 degrees C are unable to aggregate or to bind monoclonal antibodies specific for the IIb-IIIa complex. To determine whether this is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(25 citation statements)
references
References 22 publications
3
22
0
Order By: Relevance
“…Subunit association is noncovalent, and calcium is required to maintain the heterodimeric structure. [12][13][14] In a notable contribution, Calvete et al 15,16 have recently placed the disulfide linkages within GPIIb and GPIIIa. Mature GPIIIa consists of 762 amino acids.…”
Section: Structure Of Gpiib-iiiamentioning
confidence: 99%
“…Subunit association is noncovalent, and calcium is required to maintain the heterodimeric structure. [12][13][14] In a notable contribution, Calvete et al 15,16 have recently placed the disulfide linkages within GPIIb and GPIIIa. Mature GPIIIa consists of 762 amino acids.…”
Section: Structure Of Gpiib-iiiamentioning
confidence: 99%
“…The concentration of ionized calcium can also in_uence the formation of GPIIb/IIIa heterodimers [23], and the GPIIb/IIIa and brinogen interaction [5]. Human platelets incubated with the extracellular calcium chelators, EDTA and EGTA, undergo morphological changes [1] and fail to aggregate [2,3,24], or bind to~brinogen in response to ADP [9,20,22]. Winters et al [25] demonstrated that the binding of MoAb 10E5, a complex speci~c anti-GPIIb/IIIa antibody, to the platelets was reduced by 80% under the conditions of complete absence of calcium and a temperature of 37ЊC.…”
Section: Discussionmentioning
confidence: 99%
“…The ex vivo platelet aggregation assay utilizes trisodium citrate as the conventional anticoagulant for the collection of whole blood to be used for the preparation of platelet-rich plasma (PRP). Unfortunately, the reduction or removal of the ionized calcium concentration from the PRP by trisodium citrate induces a morphological change in the platelets [1] and in_uences the stability of the GPIIb/IIIa complex [2][3][4] and the divalent cation-dependent binding of RGD ligands to the GPIIb/IIIa receptor [5,6]. Under such circumstances, the ex vivo platelet aggreagation studies may falsely reveal a greater antiplatelet potency of a particular antagonist of the glycoprotein receptor.…”
mentioning
confidence: 99%
“…4 shows the results of similar experiments (excitation wavelength 360 nm) conducted using ADP (10,M) as agonist. MnCl2 was added before addition of ADP, since the opening of divalent channels appears to be more transient when ADP is the agonist (Shattil et al, 1985;Rink, 1988). In all cases, ADP-induced Mn2+ influx was not detectably altered by the presence of the monoclonal Platelets were prelabelled with [3H]adenine as indicated in the Materials and methods section and challenged with (a) albolabrin (400 nm final) or (b) elegantin (400 nm final) in the absence or presence of a phosphodiesterase inhibitor (5 mM-IBMX).…”
Section: Fig 4 Effects Of Albolabrin and Monoclonal Antibody Inducementioning
confidence: 99%
“…The fibrinogen receptor activity of the complex is only expressed in activated platelets and is essential for platelet aggregation. Based on studies of platelets from thrombasthenic patients, which lack GPIIb-IIIa, and studies with complex-specific monoclonal antibodies, it was proposed that the integrity of the GPIIb-IIIa dimer is important for Ca2+ homeostasis in unstimulated human platelets (Brass, 1984(Brass, , 1985Shattil et al, 1985). Using other monoclonal antibodies directed against GPIIb-IIIa, Powling & Hardisty (1985) investigated the possibility that this complex might serve as a Ca2+ channel in stimulated platelets.…”
Section: Introductionmentioning
confidence: 99%